A Comparative Study of Bhavacakra Painting - Tamang, Deepak Dong (Historical Journal, 2020)
The Bhavacakra is a symbolic representation of Samsara, a powerful mirror for spiritual aspirants and it is often painted to the left of Tibetan monastery doors. Bhavacakra, ‘wheel of life’ consists of two Sanskrit words ‘Bhava’ and ‘Cakra’. The word bhava means birth, origin, existing etc and cakra means wheel, circle, round, etc. There are some textual materials which suggest that the Bhavacakra painting began during the Buddha lifetime. Bhavacakra is very famous for wall and cloth painting. It is believed to represent the knowledge of release from suffering gained by Gautama Buddha in the course of his meditation. This symbolic representation of Bhavacakra serves as a wonderful summary of what Buddhism is, and also reminds that every action has consequences. It can be also understood by the illiterate persons not needing high education and it shows the path of enlightenment out of suffering in samsara. Mahayana Buddhism is very popular in Asian countries like northern Nepal, India, Bhutan, China, Korean, Japan and Mongolia. So in these countries every Mahayana monastery there is wall painting and Thānkā painting of Bhavacakra. But in these countries there are various designs of Bhavacakra due to artist, culture and nation.